[11C]Doxepin binding to histamine H1 receptors in living human brain: reproducibility during attentive waking and circadian rhythm - Yanai, Kazuhiko (Frontiers in Systems Neuroscience, 2012)
Molecular imaging in neuroscience is a new research field that enables visualization of the impact of molecular events on brain structure and function in humans. While magnetic resonance-based imaging techniques can provide complex information at the level of system, positron emission tomography (PET) enables determination of the distribution and density of receptor and enzyme in the human brain. Previous studies using [11C]raclopride revealed that the release of neuronal dopamine was increased in human brain by psychostimulants or reward stimuli. Following on from these previous studies, we examined whether the levels of neuronal release of histamine might change [11C]doxepin binding to the H1 receptors under the influence of physiological stimuli. The purpose of the present study was to evaluate the test-retest reliability of quantitative measurement of [11C]doxepin binding between morning and afternoon and between resting and attentive waking conditions in healthy human subjects. There was a trend for a decrease in [11C]doxepin binding during attentive calculation tasks compared with that in resting conditions, but the difference (approximately 10%) was not significant. In contrast, the binding potential of [11C]doxepin in the anterior cingulate gyrus was significantly higher in the morning than that in the afternoon (approximately 19%), suggesting that higher histamine release in the morning would decrease the [11C]doxepin binding in the afternoon. This study suggests that non-invasive measurement of neuronal histamine release is feasible in humans by PET ligand-activation study, although the development of a tracer with better signal-to-noise properties is needed.